Inflammatory‐sensitive CHI3L1 protects nucleus pulposus via AKT3 signaling during intervertebral disc degeneration. Issue 3 (29th January 2020) - Wang, Ruizhe; Xu, Chen; Zhong, Huajian; Hu, Bo; Wei, Leixin; Liu, Ning; Zhang, Yizhi; Shi, Qianghui; Wang, Chen; Qi, Min; Gu, Yifei; Shen, Xiaolong; et al.
Abstract: Intervertebral disc degeneration (IDD) is the main cause of low back pain and the mechanism of which is far from fully revealed. Although inflammation directed nucleus pulposus (NP) extracellular matrix metabolism dysregulation is known to be the main cause of the degeneration process, few is known about the protective factors. Using high‐throughput label‐free proteomics, we found that inflammation‐related autocrine factor Chitinase‐3‐like protein 1 (CHI3L1, or YKL‐40) is highly expressed in the NP cells during degeneration. Immunohistochemical analysis show that the expression of CHI3L1 is NP tissue specific, and increase significantly during degeneration. Overexpression of CHI3L1 significantly decrease the catabolism, and increase the anabolism of extracellular matrix. Knockdown of CHI3L1 using siRNAs show the opposite results, which imply that the protective role of CHI3L1 in IDD. Using high‐throughput RNA sequencing and functional analyses, we find that AKT3 expression and its phosphorylation is mainly regulated by CHI3L1. And lastly, the mechanism of which is also validated using human and mouse degenerated NP tissues. In summary, our findings show that the inflammation‐related autocrine factor CHI3L1 is NP specific, and it protects IDD by promoting the AKT3 signaling, which may serve as a potential therapeutic target in intervertebral disc degeneration.